Analisis Efektivitas Penggunaan Fintech Terhadap Pendapatan UMKM di Tulungagung: Studi Kasus Dinova Store - Moch. Zainul Arif; Fikri Dwi Anto; Sri Rahayu; Naela Karima (Universitas 17 Agustus 1945 Semarang, 2024)
The purpose of this study was to determine the effectiveness of financial technology on the income level of Micro, Small, and Medium Enterprises (MSMEs) in Tulungagung. This research was conducted as a case study of Dinova Store, an accessories shop. Data was collected through documentation. Data analysis employed the nonparametric Mann-Whitney U test. Based on the research results, the Asymp. Sig. (2-tailed) value of 0.004 is less than 0.05, indicating a significant difference in sales levels between using fintech and conventional methods. Therefore, further investigation into the difference in sales levels can be conducted by focusing on the mean posttest values. The results show that sales using fintech are higher compared to using cash or conventional systems.